Maternal and perinatal outcome in eclampsia complicated by posterior reversible encephalopathy syndrome; a three years’ experience in a tertiary care hospital - Karanth, Shashikala Karanth; Gonsalves, Kavitha; C. N., Sheela; Mathew, Reena; Sarma, G. R. K.; Phillip, Babu; Sumithra, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: PRES can be associated with number of medical conditions and was observed frequently in patients with preeclampsia and eclampsia. Neuroimaging is important for the diagnosis of PRES. Study was conducted to find out the maternal and perinatal outcome in patients with eclampsia complicated by posterior reversible encephalopathy syndrome (PRES). Methods: This is a retrospective study done at St. Johns Medical College Bangalore, between October 2013 and October 2016. We reviewed case records of all the patients with eclampsia who underwent neuro imaging studies and a diagnosis of PRES was made. The maternal and perinatal outcomes in these women were studied Results: In the past three years we had 55 cases of eclampsia who underwent neuroimaging studies for persistent neurological symptoms after 24 hours of MgSO4 treatment. Of these women 30 were diagnosed to have PRES. In the present study PRES was common in multiparous women and more in patients with antepartum eclamptic women. Mean age at diagnosis of PRES was 26±5.1 years. Common presenting symptoms were headache (93.3%) and vomiting (53.3%). The mean SBP/DBP was 180/110 mmHg. All patients who had recurrent seizures were controlled with MgSO4 alone. 53.3% of our patients had eclampsia related complications and 36.7% required ICU care. There were 3 maternal deaths (10%). Perinatal mortality was 20%. Conclusions: Neuroimaging in eclamptic patients with persistent neurological symptoms could help in early diagnosis of PRES and multidisciplinary approach in management could contribute significantly in reducing the maternal mortality and morbidity.